DigiTrainer: Hi-tech measurement system for kayak-canoe - Grand, L.; Gerber, B. (2009)
Presentation of the functions and advantages of the hightech measurement system DigiTrainer (Polaris Ltd.) for kayak-canoe as an effective gadget to help to train athletes.